Diseño del sistema de acondicionamiento de aire para el Auditorio Judicial Miguel Blanco Quirós del Organismo de Investigación Judicial - Mata-Bonilla, Mario José (Instituto Tecnológico de Costa Rica, 2017)
The purpose of this project is to design the air conditioning system for the Miguel Blanco Quirós Judicial Auditorium of the OIJ, whose problem is that there is currently a system that does not comply with the environmental aspects that the country has committed to adopt, in addition to having an age of 15 years whose deterioration has increased over time, which has caused the system to be subject to continuous repairs. In order to solve the aforementioned problem, the thermal load of the enclosure was calculated, the pipeline and duct system was sized, the generation equipment and terminal units were selected, the design drawings were drawn up and the project budget analysis was carried out, all in accordance with design criteria of the ASHRAE Standard, as well as with the legal framework that governs the health and environmental aspects in this type of designs. It was determined that the energy to be compensated by the system is 107.001,23 kcal/h (35,36 tons of refrigeration) and its calculation was verified by thermal load calculation software, which the project cost is $ 133.298 (₡ 76.294.443,28) and that the savings to implement the project is 21,39%, equivalent to about ₡ 275.498,58 per month and to ₡ 3.305.982,93 per year with respect to the system currently installed. It was determined that the project has a value of $ 3.769,64/Ton (₡ 2.157.589,52/Ton), a cost per area of $ 297,89/m2 (₡ 170.500,90/m2) and a cost of $ 305,03/occupant (₡ 174.586,83/occupant).
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Aire; Agua; Carga; ASHRAE; Refrigeración; Research Subject Categories::TECHNOLOGY::Engineering mechanics::Mechanical manufacturing engineering